Functional Foods and Food Supplements - Turrini, Federica; Boggia, Raffaella; Zunin, Paola (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Recent technological advancements, socio-economic trends, and population lifestyle modifications throughout the world indicate the need for foods with increased health benefits. The clear relationship between the food that we eat and our well-being is widely recognized. Today, foods are not only intended to satisfy hunger and provide necessary nutrients: they can also confer additional health benefits, such as preventing nutrition-related diseases and improving physical and mental well-being. This book provides a comprehensive overview of developments in the field of functional foods and food supplements. Readers will discover new food matrices as innovative natural sources of bioactive compounds endowed with health-promoting properties. Studies on chemical, technological, and nutritional characteristics of healthy food ingredients, analytical methods for monitoring their quality, and innovative formulation strategies are included.